Design and Development of Sports Management Information System based on Acceleration Transducer - Yongxin Wang; Honghong Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper analyses and compares the acceleration sensor: ADXL330, ADXL345, ADXL203, and points out that the acceleration sensor functions in sports management system. Sports management system is the main controller in motion process command each node controller through the sensor to collect the movement process of the ADXL system the human body each point in three coordinate axes acceleration component. The article presents design and development of sports management information system based on acceleration transducer. Design of sports information management system based on three axis accelerometer can quickly and accurately collect human motion information, which provides a new method for the study of sports.